Sustainable fashion: an exploratory study to understand the issues and challenges faced by sustainable fashion industry in Malaysia - Surindar Singh, Satpal Singh A/L (2018)
This is an exploratory study that aims to understand the issues and challenges faced by the sustainable fashion industry in Malaysia. Using information gathered from industry players, literature review and the qualitative research, this study will also propose recommendations to further promote sustainable fashion in Malaysia.